An antimicrobial helix A-derived peptide of heparin cofactor II blocks endotoxin responses in vivo - Papareddy, Praveen (2014)
Host defense peptides are key components of the innate immune system, providing multi-facetted responses to invading pathogens. Here, we describe that the peptide GKS26 (GKSRIQRLNILNAKFAFNLYRVLKDQ), corresponding to the A domain of heparin cofactor II (HCII), ameliorates experimental septic shock. The peptide displays antimicrobial effects through direct membrane disruption, also at physiological salt concentration and in the presence of plasma and serum. Biophysical investigations of model lipid membranes showed the antimicrobial action of GKS26 to be mirrored by peptide incorporation into, and disordering of, bacterial lipid membranes. GKS26 furthermore binds extensively to bacterial lipopolysaccharide (LPS), as well as its endotoxic lipid A moiety, and displays potent anti-inflammatory effects, both in vitro and in vivo. Thus, for mice challenged with ip injection of LPS, GKS26 suppresses pro-inflammatory cytokines, reduces vascular leakage and infiltration in lung tissue, and normalizes coagulation. Together, these findings suggest that GKS26 may be of interest for further investigations as therapeutic against severe infections and septic shock.